The stereoscopic advantage for vection persists despite reversed disparity - Palmisano, Stephen; Nakamura, Shinji; Allison, Robert S.; Riecke, Bernhard E. (Attention, Perception, & Psychophysics, 2020)
Research has shown that consistent stereoscopic information improves the vection (i.e. illusions of self-motion) induced in stationary observers. This study investigates the effects of placing stereoscopic information into direct conflict with monocular motion signals by swapping the observer’s left and right eye views to reverse disparity. Experiments compared the vection induced by stereo-consistent, stereo-reversed and flat-stereo patterns of: (1) same-size optic flow, which contained monocular motion perspective information about self-motion, and (2) changing-size optic flow, which provided additional monocular information about motion-in-depth based on local changes in object image sizes. As expected, consistent stereoscopic information improved the vection-in-depth induced by both changing-size and same-size patterns of optic flow. Unexpectedly, stereo-reversed patterns of same-size optic flow also induced stronger vection-in-depth than flat-stereo patterns of same-size optic flow. The effects of stereo-consistent and stereo-reversed information on vection strength were found to correlate reliably with their effects on perceived motion-in-depth and motion after-effect durations, but not with their effects on perceived scene depth. This suggests that stereo-consistent and stereo-reversed advantages for vection were both due to effects on perceived motion-in-depth. The current findings clearly demonstrate that stereoscopic information does not need to be consistent with monocular motion signals in order to improve vection. When taken together with past findings, they suggest that stereoscopic information only needs to be dynamic (as opposed to static) in order to improve vection-in-depth.
Keywords: journalPaper